Severe thrombocytopaenia in patients with vivax malaria compared to falciparum malaria: a systematic review and meta-analysis - Cho Naing; Maxine A. Whittaker (BMC, 2018)
Abstract Background Plasmodium vivax is the most geographically widespread species among human malaria parasites. Immunopathological studies have shown that platelets are an important component of the host innate immune response against malaria infections. The objectives of this study were to quantify thrombocytopaenia in P. vivax malaria patients and to determine the associated risks of severe thrombocytopaenia in patients with vivax malaria compared to patients with P. falciparum malaria. Main body A systematic review and meta-analysis of the available literature on thrombocytopaenia in P. vivax malaria patients was undertaken. Relevant studies in health-related electronic databases were identified and reviewed. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Fifty-eight observational studies (n = 29 664) were included in the current review. Severe thrombocytopaenia (< 50 000/mm3) to very severe thrombocytopaenia (< 20 000/mm3) was observed in 10.1% of patients with P. vivax infection. A meta-analysis of 11 observational studies showed an equal risk of developing severe/very severe thrombocytopaenia between the patients with P. vivax malaria and those with P. falciparum malaria (OR: 1.98, 95% CI: 0.92-4.25). This indicates that thrombocytopaenia is as equally a common manifestation in P. vivax and P. falciparum malaria patients. One study showed a higher risk of developing very severe thrombocytopaenia in children with severe P. vivax malaria than with severe P. falciparum malaria (OR: 2.80, 95% CI: 1.48-5.29). However, a pooled analysis of two studies showed an equal risk among adult severe cases (OR: 1.19, 95% CI: 0.51-2.77). This indicates that the risk of developing thrombocytopaenia in P. vivax malaria can vary with immune status in both children and adults. One study reported higher levels of urea and serum bilirubin in patients with P. vivax malaria and severe thrombocytopaenia compared with patients mild thrombocytopaenia or no thrombocytopaenia, (P < 0.001 in all comparisons). A pooled analysis of two other studies showed a similar proportion of bleeding episodes with thrombocytopaenia in severe P. vivax patients and severe P. falciparum patients (P = 0.09). This implied that both P. vivax and P. falciparum infections could present with bleeding episodes, if there had been a change in platelet counts in the infected patients. A pooled analysis of another two studies showed an equal risk of mortality with severe thrombocytopaenia in both P. vivax and P. falciparum malaria patients (OR: 1.16, 95% CI: 0.30-4.60). However, due to the low number of studies with small sample sizes within the subset of studies that provided clinically relevant information, our confidence in the estimates is limited. Conclusion The current review has provided some evidence of the clinical relevance of severe thrombocytopaenia in P. vivax malaria. To substantiate these findings, there is a need for well designed, large-scale, prospective studies among patients infected with P. vivax. These should include patients from different countries and epidemiological settings with various age and gender groups represented.